Analisis Diskriminan Terhadap Pengelompokan Mutu Pendidikan Sekolah Menengah Atas di Kabupaten Lamongan - Mu’tasim Billah; Novita Eka Chandra; Siti Amiroch (Unisda Journal of Mathematics and Computer Science (UJMC), 2020)
Quality of education is the educational services ability that can fill the needs or expectations, satisfaction internally and externally which includes educational inputs, processes and outputs. The purpose of this reserach is to classify the quality of high school education in Lamongan District using factor, cluster and discriminant analysis. The dominant factors of 12 education quality variables can be known from the results of factor analysis using the PCA (Principal Component Analysis) method. The grouping of 48 high schools did by cluster analysis using 5 hierarchical methods. The validity index used to determine the optimal group number of the five hierarchical methods is RMSSTD (Root Mean Square Standard Deviation). The classification accuracy testing uses discriminant analysis based on the results of factor analysis and cluster analysis. Grouping the quality of education is influenced by dominant factors such as the number of classrooms, the value of accreditation, the number of certification and non-certification teachers, the number of education staff, the ratio of students to teachers, the number of laboratory rooms that can be known from the results of factor analysis. In cluster analysis, using the Mahalanobis distance because there is multicollinearity and the smallest RMSSTD index value obtained in the Complete Linkage method with 5 clusters. So, with discriminant analysis, it can be concluded that the grouping based on factor analysis and cluster analysis is 58.3% of the 48 processed data that has been entered in the group that matches the original data.